Água para todos: avaliação qualitativa do processo de implementação do Plano Nacional de Recursos Hídricos - João Bosco Senra (2014)
The Federal Government, through the Department of Water Resources, current Department of Water Resources and Urban Environment, with support from the National Water Agency, coordinated the preparation of the National Water Resources Plan, approved in 2006 , which had from the beginning the concern to incorporate strategies and mechanisms that might reasonably ensure their implementation. This research aims to analyze, retrospectively and prospectively, the process of implementation of the National Water Resources Plan in order to assess the effectiveness of the proposed strategy and achievements. The methodology used in the interviews, the policy Delphi panel, and a workshop with participation of experts with extensive knowledge and engagement in the area of water resources, allowed to present: views on the historical process of drafting the National Plan Water Resources; challenges, and proposals for revision procedures and their implementation. The results confirmed the hypotheses and fulfill the specific research objectives and presents a number of significant issues that may serve other future studies on the topics of Water Resources. Among these we can mention, for example, those who: propose to expand the involvement of various stakeholders in the implementation of PNRH through the creation of dialogic channels, with involvement of the twelve regions hydrographic process; improve the representativeness of the various sectors, and expand the participation of the other Ministries in conjunction with the plans of the various users. In conclusion, among others, that: the process of preparing the National Water Resources Plan was innovative and mobilizer; considered the water in its various technical, economic, political and symbolic dimensions; contributed to a culture of planning water resources management in Brazil, in a participatory manner, for the installation process collegiate water resources period and methodology revision of the National Water Resources Plan should be reviewed, and that the inclusion of its shares in the Multi-Year Plan of the Federal Government was very important. Join finally that the methodology for their preparation may be employed for the construction of other National Plans.